Natural selection based on coordination chemistry: computational assessment of [4Fe–4S]-maquettes with non-coded amino acids. Issue 6 (18th October 2019) - Szilagyi, Robert K.; Hanscam, Rebecca; Shepard, Eric M.; McGlynn, Shawn E.
Abstract : Cysteine is the only coded amino acid in biology that contains a thiol functional group. Deprotonated thiolate is essential for anchoring iron–sulfur ([Fe–S]) clusters, as prosthetic groups to the protein matrix. [Fe–S] metalloproteins and metalloenzymes are involved in biological electron transfer, radical chemistry, small molecule activation and signalling. These are key metabolic and regulatory processes that would likely have been present in the earliest organisms. In the context of emergence of life theories, the selection and evolution of the cysteine-specific R–CH2 –SH side chain is a fascinating question to confront. We undertook a computational [4Fe–4S]-maquette modelling approach to evaluate how side chain length can influence [Fe–S] cluster binding and stability in short 7-mer and long 16-mer peptides, which contained either thioglycine, cysteine or homocysteine. Force field-based molecular dynamics simulations for [4Fe–4S] cluster nest formation were supplemented with density functional theory calculations of a ligand-exchange reaction between a preassembled cluster and the peptide. Secondary structure analysis revealed that peptides with cysteine are found with greater frequency nested to bind preformed [4Fe–4S] clusters. Additionally, the presence of the single methylene group in cysteine ligands mitigates the steric bulk, maintains the H-bonding and dipole network, and provides covalent Fe–S(thiolate) bonds that together create the optimal electronic and geometric structural conditions for [4Fe–4S] cluster binding compared to thioglycine or homocysteine ligands. Our theoretical work forms an experimentally testable hypothesis of the natural selection of cysteine through coordination chemistry.